2015
DOI: 10.1159/000441504
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Alleviates Peritoneal Fibrosis via Attenuating Inflammation and TGF-β1 Synthesis

Abstract: Background/Aims: Peritoneal fibrosis is one of the long-term complications in peritoneal dialysis (PD) patients. Recent evidences have suggested that hydrogen sulfide (H2S) is beneficial in treating various fibrotic diseases, including pulmonary fibrosis, cirrhosis, kidney fibrosis and cardiac hypertrophy. However, no information is known about the effect of H2S on peritoneal fibrosis. In the present study, we investigated the effect of H2S on peritoneal fibrosis and explored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The irreversible and progressive pulmonary fibrosis leading to respiratory function failure is still the main cause of PQ‐induced death (Dinis‐Oliveira et al, ). Recently, increasing evidence indicates that plasma H 2 S is low level in several animal models of fibrotic diseases and a supplement of exogenous H 2 S is able to ameliorate fibrosis in the kidney (Han et al, ; L. Li et al, ; Li, Li, Zeng, Liu, & Yang, ), heart (Li et al, ; Liang et al, ; Liu et al, ), liver (Mani, Cao, Wu, & Wang, ), peritoneum (Lu et al, ), skin and lung (Fang et al, ; Wang et al, ). As a significant process towards fibrogenesis, EMT characterizes the morphological changes associated with the downregulation of epithelial cell markers, such as E‐cadherin, and upregulation of mesenchymal markers, such as vimentin (Cannito et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The irreversible and progressive pulmonary fibrosis leading to respiratory function failure is still the main cause of PQ‐induced death (Dinis‐Oliveira et al, ). Recently, increasing evidence indicates that plasma H 2 S is low level in several animal models of fibrotic diseases and a supplement of exogenous H 2 S is able to ameliorate fibrosis in the kidney (Han et al, ; L. Li et al, ; Li, Li, Zeng, Liu, & Yang, ), heart (Li et al, ; Liang et al, ; Liu et al, ), liver (Mani, Cao, Wu, & Wang, ), peritoneum (Lu et al, ), skin and lung (Fang et al, ; Wang et al, ). As a significant process towards fibrogenesis, EMT characterizes the morphological changes associated with the downregulation of epithelial cell markers, such as E‐cadherin, and upregulation of mesenchymal markers, such as vimentin (Cannito et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, it was discovered that endogenous H 2 S participated in anti-inflammation, anti-oxidation, and the regulation of cell proliferation and apoptosis (Gao et al 2012 ; Moody and Calvert 2011 ; Vandiver and Snyder 2012 ). Past studies have confirmed that exogenous H 2 S attenuates aortic-coarctation-induced cardiac hypertrophy and fibrosis (Huang et al 2012 ), inhibit renal interstitial fibrosis caused by obstructive nephropathy (Song et al 2014 ), relieve peritoneal mesothelial cell injury caused by high-glucose peritoneal dialysis fluids (Lu et al 2015 ) and carbon tetrachloride-induced cirrhosis (Tan et al 2011 ). The potential mechanisms of H 2 S anti-fibrotic may be account for inhibiting the activation and migration of inflammatory cells likewise myofibroblasts, subsequently decrease the production of pro-inflammatory cytokines and extracellular matrix accumulation (Li et al 2008 ; Tan et al 2011 ).…”
Section: Introductionmentioning
confidence: 94%
“…In a study by Hou et al (), exogenous H 2 S can partially prevent ageing‐related kidney dysfunction by decreasing collagen deposition in mice. A recent study demonstrated that H 2 S alleviated peritoneal fibrosis via attenuating inflammation (Lu et al, ). The finding suggests that the antifibrotic effects of NaHS through NF‐κB and H 2 S pathways may contribute to the amelioration of diminished erectile function related to hypertension.…”
Section: Discussionmentioning
confidence: 99%